From survival of irradiated mice to modern molecular insights: a seventy-year journey in radiobiology at the institute of biophysics, Czech academy of sciences - Toufar, Jiří; Toufarová, Lucie; Falková, Iva; Bačíková, Alena; Falk, Martin (European biophysics journal, 2025)
This paper has been prepared to commemorate the 70th anniversary of the Institute of Biophysics of the Czech Academy of Sciences (IBP CAS), which has a long-standing tradition in researching the biological effects of ionizing radiation (IR). Radiobiology has recently gained renewed importance due to several compelling factors. The demand for a better understanding of the biological effects of both low and high doses of various types of ionizing radiation, along with improved radiation protection, is increasing-particularly in the context of critical ongoing human activities such as medical diagnostics, radiotherapy, and the operation of nuclear power plants. This demand also extends to newly emerging scenarios, including the development of hadron and FLASH radiotherapy, as well as mixed radiation field exposures related to planned manned missions to Mars. Unfortunately, there is also an urgent need to address the heightened risk of nuclear materials and weapons misuse by terrorists or even rogue states. Additionally, nuclear energy is currently the only viable alternative that can provide efficient, sustainable, and ecological coverage for the dramatically increasing current and future energy demands. Understanding the risks of IR exposure necessitates exploring how different types of IR interact with living organisms at the most fundamental level of complexity, specifically at the level of molecules and their complexes. The rising interest in radiobiology is, therefore, also driven by new experimental opportunities that enable research at previously unimaginable levels of detail and complexity. In this manuscript, we will address the important questions in radiobiology, focusing specifically on the mechanisms of radiation-induced DNA damage and repair within the context of chromatin architecture. We will emphasize the differing effects of photon and high-LET particle radiation on chromatin and DNA. Both forms of IR are encountered on Earth but are particularly significant in space.
Keywords: Densely ionizing (high-LET) particle radiation; Photon radiation; Institute of biophysics of the Czech academy of sciences; DNA damage and repair; Biological effects of ionizing radiation; Microscopy; Radiobiological research; Chromatin architecture at micro- and nano-scale; Single molecule localization microscopy (SMLM)